Fatigue life evaluation for carbon/epoxy laminate composites under constant and variable block loading - Reis, P. N. B. (2009)
http://www.sciencedirect.com/science/article/B6TWT-4TN82M4-1/2/ffb1a17eaf7390463ad097c3ba5d4e8f